2016
DOI: 10.1038/srep33059
|View full text |Cite
|
Sign up to set email alerts
|

Gene deleted live attenuated Leishmania vaccine candidates against visceral leishmaniasis elicit pro-inflammatory cytokines response in human PBMCs

Abstract: Currently no effective vaccine is available for human visceral leishmaniasis(VL) caused by Leishmania donovani. Previously, we showed that centrin1 and p27gene deleted live attenuated Leishmania parasites (LdCen1−/− and Ldp27−/−) are safe, immunogenic and protective in animal models. Here, to assess the correlates of protection, we evaluated immune responses induced by LdCen1−/− and Ldp27−/− in human blood samples obtained from healthy, healed VL (HVL), post kala-azar dermal leishmaniasis(PKDL) and VL subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
(90 reference statements)
2
23
0
Order By: Relevance
“…The CD200 blocking directed CD200R + T cells to acquire Th1-type functional characteristics that further suggested that reduced CD200-CD200R expression may help antigen experience CD4 + T cells to produce inflammatory cytokines as observed in LdCen −/− -immunized animals. We have previously reported strong protection abilities of these parasites and herein provide one of the possible mechanisms via control of coinhibitory molecules such as CD200 and CD200R, resulting in CD4 + T cells to acquire Th1-type multi-functionality ( 10 14 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The CD200 blocking directed CD200R + T cells to acquire Th1-type functional characteristics that further suggested that reduced CD200-CD200R expression may help antigen experience CD4 + T cells to produce inflammatory cytokines as observed in LdCen −/− -immunized animals. We have previously reported strong protection abilities of these parasites and herein provide one of the possible mechanisms via control of coinhibitory molecules such as CD200 and CD200R, resulting in CD4 + T cells to acquire Th1-type multi-functionality ( 10 14 ).…”
Section: Discussionmentioning
confidence: 83%
“…Of the various vaccine formulations tested, live attenuated parasites allow host immune system to interact with a broad repertoire of antigens, which is considered to be essential for the development of protective immunity, and importantly cause no pathology. We have reported on centrin-deleted L. donovani parasites (LdCen −/− ) as live attenuated vaccines in various animal models and in ex vivo human studies ( 10 14 ). LdCen −/− parasites induce multiple cytokine (IFNγ, IL-2, and TNFα)-secreting Th1 cells in the immunized mice, a response shown to be the best predictor of protective immunity ( 11 , 12 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of these parasite lines with centrin1 gene deletion from a L. donovani strain ( LdCen −/− ) has been characterized extensively ( 15 , 16 , 19 , 20 ) with the LdCen −/− parasites showing 5–8 weeks persistence in mice ( 15 ). Our preclinical evaluations demonstrated the safety, immunogenicity characteristics of LdCen −/− parasites, and protection against infection with virulent L. donovani associated with an induction of a protective adaptive immune response in various animal models including mouse, hamster, and dog ( 15 , 19 , 20 ) and in ex vivo studies in human PBMCs in VL endemic areas ( 21 ).…”
Section: Introductionmentioning
confidence: 82%
“…Genetically modified live-attenuated L. donovani Δ Ldcen and Δ Ldp27 has been described as vaccine candidates 10 , 42 , 43 , but also several targets have been implicated in loss of virulence upon disruption in different Leishmania species that often elicit protective immunity in vivo such as: silent information regulator (SIR2) 44 , A2 45 , arabino-1,4-lactone oxidase 9 and biopterin transporter BT1 46 , 47 in L. donovani ; HSP70-II in L. infantum 48 ; mitochondrial superoxide dismutase in L. amazonensis 49 ; δ-amastins in L. braziliensis 50 and cysteine protease B in L. mexicana 51 …”
Section: Discussionmentioning
confidence: 99%